MOBILE AGENT APPLICATION DEVELOPMENT IN A SIMPLE JAVA-BASED MOBILE AGENT SYSTEM (SIMMAS) - Osunade, O.; Oloritun, R. D. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
As network information resources grew in size, it was most efficient to process queries and updates at the site where the data was located. The processing accomplished by a traditional client-server network interface constrained the client to the set of queries supported by the server, or required the server to send all data to the client for processing. The former was inflexible and the latter was inefficient. Mobile agents support the movement of the client computation to the location of the remote resource. It has the potential to be flexible and efficient. Mobile agents are capable of suspending their execution, transporting themselves to another host on a network, and resuming execution from the point at which they were suspended. Mobile agents consume fewer network resources and support systems that do not have permanent network connections, such as mobile computers and personal digital assistants. This work described a prototype java based mobile agent environment for the development and deployment of mobile agent applications. The prototype called SIMMAS allowed programmer-developed applications to inherit mobility.